2016
DOI: 10.3390/met6090199
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Evolution of Light Weight High Entropy Alloys: A Review

Abstract: High Entropy Alloys (HEAs) are the most recently developed new class of materials, which are known for their unique structural properties. Lightweight materials are currently in excessive demand for transportation and energy saving applications. In this review, efforts have been made to summarize the work done towards the development of HEAs targeting lightweight applications. Some new synthesis techniques are suggested for the fabrication of lightweight HEAs (LWHEAs). The concept of porous structure fabricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(56 citation statements)
references
References 94 publications
0
56
0
Order By: Relevance
“…For the likelihood of having a simplified microstructure besides having many elements, HEAS should have entropy of mixing in the range of 11 ≤ ΔS mix ≤ 19.5 J/K mol and enthalpy of mixing in the range of −22 ≤ ΔH mix ≤ 7 kJ/mol [32]. Initially HEAs were developed for high temperature applications with a density hovering around 10 g/cc and later efforts were made to develop light weight HEAs [33]. Conventional processing techniques such as powder metallurgy and casting routes can be utilized for synthesizing HEAs indicating that industrial production is not a major issue but the challenge is to find the composition that suits the end application.…”
Section: High Entropy Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…For the likelihood of having a simplified microstructure besides having many elements, HEAS should have entropy of mixing in the range of 11 ≤ ΔS mix ≤ 19.5 J/K mol and enthalpy of mixing in the range of −22 ≤ ΔH mix ≤ 7 kJ/mol [32]. Initially HEAs were developed for high temperature applications with a density hovering around 10 g/cc and later efforts were made to develop light weight HEAs [33]. Conventional processing techniques such as powder metallurgy and casting routes can be utilized for synthesizing HEAs indicating that industrial production is not a major issue but the challenge is to find the composition that suits the end application.…”
Section: High Entropy Alloysmentioning
confidence: 99%
“…Conventional processing techniques such as powder metallurgy and casting routes can be utilized for synthesizing HEAs indicating that industrial production is not a major issue but the challenge is to find the composition that suits the end application. Table 4 provides HEAs processed using different methods and with different densities and crystal structure [33].…”
Section: High Entropy Alloysmentioning
confidence: 99%
“…High-entropy alloys [3,[19][20][21][22] and high-entropy nano-alloys [23,24] have not been used as a practical coating in the mineral industry in any form so far. The extraordinary characteristics of high-entropy alloys in can be made us of in heavy industries [25][26][27][28][29][30][31][32][33][34][35][36][37] to produce unique compositions [38][39][40][41][42][43][44][45] and their behaviors and properties [46][47][48] can be manipulated to introduce innovative alternatives, such as filler metals [49], which are hard-facing [50][51][52] and wear resistant [53] to increase to shear failure, high cavitation erosion, and corrosion [54,55]. In general, the impact strength of hardened alloys decreases with increasing carbide content.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been reported regarding in these series of alloys, as found in the review by Pickering and Jones (2016), but research focused in light high entropy alloys is still scarce. Some of them are that by Youssef et al (2015) in AlLiMgScTi but most of them are included in the review by Kumar and Gupta (2016).…”
Section: Introductionmentioning
confidence: 99%